Ophthalmic applications of cyclopentolate - Chmielarz-Czarnocińska, Anna; Gotz-Więckowska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Cyclopentolate is a drug that causes paralysis of accommodation and induces mydriasis. It is widely used around the world. In view of its relatively short duration of action and effective induction of cycloplegia, cyclopentolate is particularly useful in screening children for refractive errors. In addition to diagnostic applications, it is also used for therapeutic purposes, e.g. in uveitis. In October 2021, cyclopentolate, which had not been approved in Poland for years, was authorized for marketing. The authors of the paper reviewed the literature on cyclopentolate. The properties of the drug were analyzed, and its action was compared with other available cycloplegic agents. In addition, the potential uses of cyclopentolate and its special role in facilitating the ophthalmological examination of children were discussed.